2019
DOI: 10.2478/sjph-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Predictors of Self-Medication with Tranquillizers and Sleeping Pills: Results of the Population-Based Study in Serbia

Abstract: Background Previous studies among the Serbian population concluded that the trend of self-medication with tranquillizers and sleeping pills requires deeper study. The objective is to identify gender differences in socio-demographic, health, and health service predictors of self-medication with tranquillizers and sleeping pills in a Serbian population of 15 years old and above. Methods This was a population-based, cross-sectional study. Data was extracted from the most recently available results of the Serbian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Comparable to our findings, females 33,34 and married participants 34 had more likelihood to practice‐self medications. These results are in concordance with self‐medication practices globally, where females showed a higher prevalence of self‐medication in general 35‐37 . Benzodiazepines were used in 14% of Chopra et al study and this was associated with high level of anxiety, but only 4% used anxiolytics in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparable to our findings, females 33,34 and married participants 34 had more likelihood to practice‐self medications. These results are in concordance with self‐medication practices globally, where females showed a higher prevalence of self‐medication in general 35‐37 . Benzodiazepines were used in 14% of Chopra et al study and this was associated with high level of anxiety, but only 4% used anxiolytics in this study.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in concordance with self-medication practices globally, where females showed a higher prevalence of self-medication in general. [35][36][37] Benzodiazepines were used in 14% of Chopra et al study and this was associated with high level of anxiety, but only 4% used anxiolytics in this study. In another study among health workers in Kenya (n = 379), 38 the prevalence of self-medication had increased unexpectedly to 60.4%, during the outbreak.…”
Section: Discussionmentioning
confidence: 94%
“…Similar studies have shown self-prescription to be a common issue among medical students; self-prescription is exacerbated by easy accessibility and the availability of several types of over-the-counter drugs, such as Panadol Night and melatonin ( 24 , 25 ). Although self-prescribed medications can have some benefits when used appropriately, it is a dangerous practice that can delay an accurate medical diagnosis and result in adverse effects, drug interactions, and developing dependence, thereby aggravating what was intended to be treated ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present research reported a high knowledge score among female students. It may be because female students more commonly self-medicate than males 41 and hence are likely to be more knowledgeable about safe medicine disposal. There is a hospital waste management guideline in Nepal according to which the wastes are managed by landfill, burial, incineration and inertization of the pharmaceutical waste product.…”
Section: Discussionmentioning
confidence: 99%